2017
DOI: 10.1155/2017/2389753
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Adipose-Derived Mesenchymal Stromal Cells Ameliorate Experimental Autoimmune Encephalomyelitis by Regulating Self-Reactive T Cell Responses and Dendritic Cell Function

Abstract: Multipotent mesenchymal stromal cells (MSCs) have emerged as a promising therapy for autoimmune diseases, including multiple sclerosis (MS). Administration of MSCs to MS patients has proven safe with signs of immunomodulation but their therapeutic efficacy remains low. The aim of the current study has been to further characterize the immunomodulatory mechanisms of adipose tissue-derived MSCs (ASCs) in vitro and in vivo using the EAE model of chronic brain inflammation in mice. We found that murine ASCs (mASCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 73 publications
1
34
0
1
Order By: Relevance
“…Thus, the concept of allogeneic stem cell therapy is becoming an ongoing reality. Indeed, in several clinical fields, such as neurology, gastroenterology, or hematology, these principles are used in experimental studies to treat different diseases like cerebral palsy [ 26 ], autoimmune encephalomyelitis [ 27 ], perianal fistulas in Crohn's disease [ 28 ], liver failure [ 29 ], and aplastic anemia [ 30 ]. The main advantages in the use of allogeneic cells in orthopedics are a greater “on-demand” availability of cell precursors, the absence of harvesting morbidity, the possibility to obtain a selected cell population, and even the possibility to use cells from younger donors for lesions in older recipient, further optimizing the quality of the repair.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the concept of allogeneic stem cell therapy is becoming an ongoing reality. Indeed, in several clinical fields, such as neurology, gastroenterology, or hematology, these principles are used in experimental studies to treat different diseases like cerebral palsy [ 26 ], autoimmune encephalomyelitis [ 27 ], perianal fistulas in Crohn's disease [ 28 ], liver failure [ 29 ], and aplastic anemia [ 30 ]. The main advantages in the use of allogeneic cells in orthopedics are a greater “on-demand” availability of cell precursors, the absence of harvesting morbidity, the possibility to obtain a selected cell population, and even the possibility to use cells from younger donors for lesions in older recipient, further optimizing the quality of the repair.…”
Section: Discussionmentioning
confidence: 99%
“…The current minimal criteria to define human MSCs are (i) plastic adherence under normal culture conditions in vitro (ii) expression of CD73, CD90 and CD105 and lack of expression of CD45, CD34, CD14 or CD11b, CD79α or CD19 and HLA-DR surface molecules and (iii) differentiation into osteoblasts, adipocytes and chondroblasts in vitro (Dominici et al, 2006 ). Although the in vivo function and differentiation potential of MSCs appear to depend on their tissue of origin (Sacchetti et al, 2016 ), in vitro expanded MSCs can migrate to sites of injury/inflammation (Kidd et al, 2009 ), secrete trophic factors and are potent regulators of the innate and adaptive immune responses in vitro and in vivo (Di Nicola et al, 2002 ; Constantin et al, 2009 ; Gonzalez-Rey et al, 2009 ; Anderson et al, 2013a , 2017 ; Gao et al, 2016 ) (Figure 2 ). Several clinical trials have evaluated the immunomodulatory and tissue regenerative potential of both autologous and allogeneic MSCs with promising results (Quarto et al, 2001 ; Connick et al, 2012 ; von Bahr et al, 2012 ).…”
Section: Multipotent Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Additional studies showed that murine AdMSCs (mASCs) suppress T-cell proliferation via inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX-2) activities. mASCs also prevented lipopolysaccharide (LPS)-induced maturation of dendritic cells (DCs) (70). The efficacy of intravenous AdMSCs transplantation in remyelination, in mouse cuprizone model of MS, can be significantly enhanced by 17β-estradiol (E2) administration (71).…”
Section: Adipose-derived Mscsmentioning
confidence: 99%